ПРОБЛЕМИ І НАПРЯМКИ МОДЕРНІЗАЦІЇ ПОДАТКОВОГО РЕГУЛЮВАННЯ В УКРАЇНІ - Десятнюк, Оксана Миронівна; Гузела, Ірина Анатоліївна (Науковий журнал «Світ фінансів», 2019)
Десятнюк О. М., Гузела І. А. Проблеми і напрямки модернізації податкового регулювання в Україні. Досліджено місце податкового регулювання у здійсненні ефективних податкових трансформацій. Визначено проблеми податкового регулювання у контексті недосконалої нормативно-правової бази оподаткування, складності процедури адміністрування податків, поширення практики ухилення від сплати податків. Окреслено напрямки модернізації податкового регулювання з орієнтуванням на оптимальне поєднання фіскальної та регулюючої функцій податків задля узгодження та гармонізації інтересів платників податків і держави. Десятнюк О. М., Гузела И. А. Проблемы и направления модернизации налогового регулирования в Украине. Исследовано место налогового регулирования в осуществлении эффективных налоговых трансформаций. Определены проблемы налогового регулирования в контексте несовершенной нормативно-правовой базы, сложности процедуры администрирования налогов, распространения практики уклонения от уплаты налогов. Определены направления модернизации налогового регулирования с ориентацией на оптимальное сочетание фискальной и регулирующей функций налогов для согласования и гармонизации интересов налогоплательщиков и государства. Desiatniuk O., Huzela I. Problems and directions of modernization of tax regulation in Ukraine. Introduction. The place of tax regulation in the implementation of effective tax transformations is investigated. The problems of tax regulation in the context of the imperfect legal and regulatory framework of taxation, the complexity of the tax administration procedure, and the spread of tax evasion practice are identified. The directions of modernization of tax regulation with orientation on optimal combination of fiscal and regulatory functions of taxes are outlined for coordination and harmonization of interests of taxpayers and the state. Purpose. The purpose of the article is to study the issues of tax regulation and outline ways of its modernization taking into account national features of the Ukrainian economy. Results. In Ukraine the first stage of modernization of tax regulation has been initiated in the context of the formation of an integrated legislative framework on taxation, institutional provision of the administration and payment procedure. At the same time, transformations in the field of tax regulation should be aimed at achieving the strategic goals of socio-economic development of the country, increase and acceleration of innovation and investment processes in the country. Conclusions. Tax regulation in Ukraine is still not an effective tool for socio-economic development of the state. An inappropriate and unjustified choice of its methods leads to a reduction in the efficiency of tax administration, an increase in their share in the expenses of enterprises, a narrowing of the tax base and the non-observance of equal competitive conditions in the economic space of the country. This, in turn, will prevent the intensification of innovation and investment processes and the achievement of high rates of socio-economic development of the state.